Work Motivation as a Mediating Factor in the Relationship Between Personality, Competence, and Employee Performance at PT Padmatirta Wisesa - Zunaidi, Imam; Sundjoto, Sundjoto; Rahayu, Sri; Fitrianty, Rifda (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This article analyzes the strategic role of work motivation in mediating the influence of personality and competence on employee performance at PT Padmatirta Wisesa, operating in the FMCG distribution industry where operational speed and service quality are crucial. Current declines in performance indicators show an urgent need to improve employee attributes and capabilities to remain competitive. A quantitative survey method was implemented, with 35 employees involved as a complete sample. The collected data were evaluated using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to measure structural relationships and mediation significance. The statistical findings demonstrate that both personality and competence have significant positive direct effects on performance, and competence is identified as the dominant factor. Moreover, motivation significantly strengthens these effects, indicating that employees’ strengths in character and knowledge must be supported by a strong intention to achieve in order to deliver superior outcomes. These insights suggest that organizations should not only focus on enhancing skills and knowledge but also design interventions that boost motivational conditions, including performance-based incentives, recognition mechanisms, and career progression accessibility. The study recommends that future investigations expand the proposed model by integrating factors such as organizational climate, workload pressure, or digital readiness to better understand performance determinants in distribution-based environments.